Situation, Impacts, and Future Challenges of Tobacco Control Policies for Youth: An Explorative Systematic Policy Review - Ranabhat, Chhabi Lal; Kim, Chun-Bae; Park, Myung Bae; Jakovljevic, Mihajlo (Michael) (Frontiers in Pharmacology, 2019)
Background Tobacco use in youths is a major public health challenge globally and approaches to the challenge, have not been sufficiently addressed. The existing policies for tobacco control are not well specified by age. Objective Our study aims to systematically investigate existing tobacco control policies, potential impacts and national and international challenges to control tobacco use targeting the youth. Data sources We used the statistics of the Global Youth Tobacco Survey (GYTS), studies and approaches of tobacco control policies targeting youth. Considering country, continent age and significance, PubMed, (Health Inter Network Access to Research Initiative (HINARI), Scopus, the Cochrane library, Google, and Google Scholar were searched. The related key words were like tobacco control, youth, smoking, smoking reduction policies, prevalence of tobacco use in youth, classification of tobacco control policies, incentives to prevent young people from using tobacco, WHO Framework Convention on Tobacco Control (FTCT) etc. Results: We found 122 studies related to this topic. There were 25 studies focusing on situation, significance and theoretical aspects of tobacco control policies associated with youth, 41 studies on national population polices and challenges and 7 studies for global challenges to overcome the youth tobacco epidemic. All national policies have been guided by WHO -MPOWER strategies. Increases in tobacco tax, warning signs on packaging, restriction of tobacco product advertisements, national law to discourage to young people, peer base approaches to quit tobacco are popular policies. Smuggling of tobacco products by youth and ignorance of smokeless tobacco control approach are major challenges. Limitation: Our study was flexible for the standard age of youth and we were not able to include all countries in the world and most of the studies focused on smoking control rather than all smokeless tobaccos. Conclusion: Due to physical and economic burden of tobacco consumption by youth, this is a high priority needing to be addressed applying creative policies. Implication of key findings: There is limited research on how and in what ways tobacco control policies reach young people, their engagement with these policies from physical, physiological and psychological aspects.